2017
DOI: 10.1111/joic.12473
|View full text |Cite
|
Sign up to set email alerts
|

Drug eluting stents are superior to bare metal stents to reduce clinical outcome and stent‐related complications in CKD patients, a systematic review, meta‐analysis and network meta‐analysis

Abstract: Aims To compare clinical outcome in Chronic kidney disease (CKD) patients receiving coronary stents according to stent type BMS versus DES and 1st generation versus 2nd generation DES. Methods and Results PubMed, Cinhal, Cochrane, Embase, and Web of Science were searched for studies including CKD patients. CKD was defined as eGFR < 60 mL/min. We selected n = 35 articles leading to 376 169 patients, of which 76 557 CKD patients receiving BMS n = 35,807, 1st generation DES n = 37,650, or 2nd generation DES n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Therefore, our results showing similar re-MI and any repeat revascularization rates between statin users and nonusers could be related to low number of enrolled patients in groups A4, B1, B3 and B4 and relatively low incidences of these events compared with previous studies [17,30]. According to recent meta-analysis data that evaluated CKD patients [40], in which CKD was defined as eGFR < 60 mL/min/1.73 m 2 , results showed that the TLR/TVR (RR, 0.69; 95% CI, 0.57-0.84) was significantly reduced with DESs compared with bare-metal stents (BMS). Additionally, the use of second-generation DESs were associated with relative 27% reduction in TLR/TVR compared with first-generation DESs.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, our results showing similar re-MI and any repeat revascularization rates between statin users and nonusers could be related to low number of enrolled patients in groups A4, B1, B3 and B4 and relatively low incidences of these events compared with previous studies [17,30]. According to recent meta-analysis data that evaluated CKD patients [40], in which CKD was defined as eGFR < 60 mL/min/1.73 m 2 , results showed that the TLR/TVR (RR, 0.69; 95% CI, 0.57-0.84) was significantly reduced with DESs compared with bare-metal stents (BMS). Additionally, the use of second-generation DESs were associated with relative 27% reduction in TLR/TVR compared with first-generation DESs.…”
Section: Discussionmentioning
confidence: 54%
“…The causes of thrombus formation and subsequent clinical events after coronary stent implantation are considered to be the accumulation of unfavorable factors in patient (eg, diabetes and hereditary drug withdrawal), procedural (eg, suboptimal stenting), device (eg, metal and polymer), lesion (eg, residual thrombus and lipid‐rich plaque), and pharmacological responses to antiplatelet drugs . Renewed technologies in G2‐DES such as biocompatible polymers, improved drug‐eluting kinetics, thinner struts, and a well‐designed platform with better conformability may contribute to the reduction of thrombus formation and clinical events compared with first‐generation DES and BMS .…”
Section: Discussionmentioning
confidence: 99%
“…The causes of thrombus formation and subsequent clinical events after coronary stent implantation are considered to be the accumulation of unfavorable factors in patient (eg, diabetes and hereditary drug withdrawal), procedural (eg, suboptimal stenting), device (eg, metal and polymer), lesion (eg, residual thrombus and lipid-rich plaque), and pharmacological responses to antiplatelet drugs. [24][25][26][27][28] Renewed technologies in G2-DES such as biocompatible polymers, improved drugeluting kinetics, thinner struts, and a well-designed platform with better conformability may contribute to the reduction of thrombus formation and clinical events compared with first-generation DES and BMS. [1][2][3][4] Although the exact mechanism of smaller thrombus burden in G2-DES compared with BMS in the present study still remains unclear, the presence of biocompatible polymer in G2-DES might play an important role as a protective factor for thrombus formation, among several differences between them.…”
Section: Thrombogenicity and Stent Characteristicsmentioning
confidence: 99%
“…22,23 Furthermore, patients with CKD exhibit increased coronary calcification, which is associated with stent malpositioning, underexpansion, and fracture. These factors may in turn predispose patients to stent thrombosis, 24,25 the rates of which dramatically increase the risk of average target lesion revascularization and mortality, whether temporary or permanent. [24][25][26] In our study, high-risk patients with ACS and CKD had no further renal dysfunction or adverse clinical complications in the short-term and at 3 months follow-up, suggesting that our protocol would benefit this extremely high-risk group (Table 3).…”
Section: Interventional Characteristicsmentioning
confidence: 99%